The impact of the Catechol-O-methyltransferase Val158Met polymorphism on survival in the general population - the HUNT study - Skorpen Frank; Stovner Lars J; Hagen Knut; Pettersen Elin; Zwart John-Anker (BMC, 2007)
Abstract Background The catechol-O-methyltransferase (COMT) gene contains a functional polymorphism, Val158Met which has been related to common diseases like cancer, psychiatric illness and myocardial infarction. Whether the Val158Met polymorphism is associated with survival has not been evaluated in the general population. The aim of this prospective study was to evaluate the impact of codon 158 COMT gene polymorphism on survival in a population-based cohort. Methods The sample comprised 2979 non-diabetic individuals who participated in the Nord-Trøndelag Health Study (HUNT) in the period 1995-97. The subjects were followed up with respect to mortality throughout year 2004. Results 212 men and 183 women died during the follow up. No association between codon 158 COMT gene polymorphism and survival was found. The unadjusted relative risk of death by non-ischemic heart diseases with Met/Met or Met/Val genotypes was 3.27 (95% confidence interval, 1.19-9.00) compared to Val/Val genotype. When we adjusted for age, gender, smoking, coffee intake and body mass index the relative risk decreased to 2.89 (95% confidence interval, 1.04-8.00). Conclusion During 10 year of follow-up, the Val158Met polymorphism had no impact on survival in a general population. Difference in mortality rates from non-ischemic heart diseases may be incidental and should be evaluated in other studies.